Bank restructuring and bank efficiency: The case of Vietnam - Xuan Vinh Vo; Nguyen Huu Huan (Cogent Economics & Finance, 2018)
This study examines the link between bank restructuring and bank efficiency in Vietnamese banks employing the Data Envelopment Analysis (DEA) and Stochastic Frontier Analysis (SFA) approach. The data sample includes 26 commercial banks over the period 1999-2015. Our finding indicates that Vietnamese government's restructuring policies in the first stage have not been beneficial for banks implementing restructuring. Regarding the effect of different restructuring methods, we show that the privatization of state-owned commercial banks, state intervention and mergers and acquisitions (M&As) do not substantially improve efficiency. Besides, we find that bank efficiency declines during bank restructuring period because of not only transition cost but also the change of other environment variables, such as financial crisis or domestic economy slowdown.
Keywords: G20; G21; 330; bank restructuring; integration; bank efficiency